Recent Advances in Gas Chromatography - Mutelet, Fabrice (IntechOpen, 2022)
Gas chromatography is one of the most used analytical techniques in the industry. It is a powerful tool with a wide range of applications. This book presents recent advances in gas chromatography, multidimensional gas chromatography, and gas chromatography mass spectrometry. It also discusses inverse gas chromatography. The main focus is the use of gas chromatography techniques to analyze petroleum fluids, biomass, and ionic liquids in medical and petrochemical industries.